Flowcytometric Immunophenotypic Profile of Acute Leukemia: Mansoura Experience - Salem, Dalia A. (Springer-Verlag, 2011)
Acute leukemia (AL) displays characteristic patterns of antigen expression, which facilitate their identification and proper classification. The purpose of this study is to evaluate the diagnostic usefulness of commonly used immune-markers for immunophenotyping of AL and to define the best immune-markers to be used for proper diagnosis and classification of AL. Besides, to recognize the frequency of different AL subtypes and the antigen expression profile in our Egyptian patients. We retrospectively analyzed the immunophenotypic data of 164 de novo AL patients from our institution during 2009 and 2010. Among these patients, 68.9% were classified as acute myeloblastic leukemia (AML) while 31.1% classified as acute lymphoblastic leukemia (ALL). The commonest FAB subtype in AML group was AML-M4/5 (34.5%) which may differ from most published data. As regard ALL, there were 74.5% with B-ALL and 25.5% with T-ALL. It was found that combined use of HLADR and CD34 was much more helpful in distinguishing APL from non-APL AML than either of these antigens alone. It was found that cCD79a and CD19 were the most sensitive marker for B-ALL while cCD3, CD7 and CD5 were the most sensitive antigens for T-ALL. Our analysis of AL phenotypes proved that employed antibody panels are adequate for proper diagnosis and classification of AL. Flowcytometry was found to be especially useful in the identification of AML-M0 and differentiation of APL from non-APL AML. Immunophenotyping results and FAB classification of our AL patients were comparable to internationally published studies apart from predominance of AML-M4/5 and more frequent APL.